Distribution systems reconfiguration based on OPF using benders decomposition - H. M. Khodr (2009)
This paper presents a new and efficient methodology for distribution network reconfiguration integrated with optimal power flow (OPF) based on a Benders decomposition approach. The objective minimizes power losses, load balancing among feeders, and is subject to constraints: capacity limit of branches, minimum and maximum power limits of substations or distributed generators, minimum deviation of bus voltages, and radial optimal operation of networks. A specific approach of the Generalized Benders decomposition algorithm is applied to solve the problem. The formulation can be embedded under two stages: the first one is the Master problem and is formulated as a mixed integer nonlinear programming problem. This stage determines the radial topology of the distribution network. The second stage is the Slave problem and is formulated as a nonlinear programming problem. This stage is used to determine the feasibility of the Master problem solution by means of an OPF and provides information to formulate the linear Benders cuts that connect both problems. The model is programmed in the General Algebraic Modeling System. The effectiveness of the proposal is demonstrated through three examples extracted from the literature.